A Bionic Spatial Cognition Model and Method for Robots Based on the Hippocampus Mechanism - Yuan, Jinsheng; Guo, Wei; Zha, Fusheng; Wang, Pengfei; Li, Mantian; Sun, Lining (Frontiers in Neurorobotics, 2022)
Hippocampus and its accessory are the main areas for spatial cognition. It can integrate path and form environmental cognition based on motion information and then realize positioning and navigation. Learning from the hippocampus mechanism is a crucial way for the research in robot perception. So it is crucial to building a calculation method that conforms to the biological principle. In addition, it should be easy to implement on a robot s. This paper proposes a bionic cognition model and method for mobile robots, which can realize precise path integration and cognition of space. Our research can provide the basis for the cognition of the environment and autonomous navigation for bionic robots.